Analisis Tingkat Kesehatan Koperasi pada Koperasi Simpan Pinjam Dharma Sari Bumi Pagutan - Nyoman Asti Primasantia; Herlina Pusparini; Indria Puspitasari Lenap (Sekolah Tinggi Ilmu Ekonomi AMM, 2023)
This research aims to analyze the health level of cooperative at KSP Dharma Sari Bumi Pagutan in 2022 using the good corporate governance, risk profile, financial performance, and capital based on the Technical Guidelines of the Deputy for Cooperative Number 15 of 2021 about Guidelines for Cooperative Health Inspection Working Papers. This research is descriptive research with quantitative approach. The data used in this study are financial statements in 2021-2022 and non-performing loan data in 2022, and answers of questionnaires. The results of this research indicate that cooperative health level at KSP Dharma Sari Bumi Pagutan in 2022 is quite healthy with total score of 77,61 overall. The score is reviewed from 4 aspects, they are good corporate governance aspect which gets 88,24 with a healthy category, risk profile aspect which gets 90,48 with a healthy category, the financial performance aspect which gets 61,11 with a under supervision category, and the capital aspect which gets 87,50 with a healthy category. The cooperative should be able to improve its performance, especially its financial performance to get a healthy category.